Pengaruh Kedisiplinan dan Kompensasi terhadap Kinerja Karyawan - Ernawati Ernawati; Arif Rachman Putra (Jurnal Simki Economic, 2021)
Employees as human resources have a role to determine the success of the company while the measure to determine the success of the company is determined by employee performance. The purpose of this study was to determine the partial and simultaneous effect of discipline and compensation variables on employee performance. The population in this study were employees in a travel and tours in the city of Surabaya, amounting to 29 people and used as a whole as respondents. The analysis tool is multiple linear regression. The research findings state that discipline has a significant influence on employee performance. Compensation also has a significant effect on employee performance. Both simultaneously affect the dependent variable.